Keeping Girls in School : A Review of the Global Evidence - Özler, Berk (World Bank, Washington, DC, 2016)
Gender gaps in education have closed in almost all countries, especially at the primary level. In fact, these gaps have reversed in many countries in secondary education, especially in Latin America, the Caribbean, and East Asia, where it is now boys and young men who are disadvantaged. Despite the overall progress, however, primary and secondary school enrollments for girls remain much lower than for boys for disadvantaged populations in many Sub-Saharan countries and some parts of South Asia (World Bank 2012). One of the key messages of the World Development Report on Gender Equality and Development is that much of the progress was possible when the removal of a single barrier was sufficient to make significant gains. Three main areas where this has been possible are: (i) increasing returns to education for women; (ii) removing institutional constraints; and (iii) increasing household incomes. In this policy brief, we summarize the extant evidence in these three areas and draw some policy conclusions.